2006
DOI: 10.1002/anie.200504594
|View full text |Cite
|
Sign up to set email alerts
|

A General and Versatile Method for CC Cross‐Coupling Synthesis of Conjugated Enynes: One‐Pot Sequence Starting from Carbonyl Compounds

Abstract: In light of the pivotal role of the carbonyl group in organic synthesis, [1] new general transformations of the carbonyl compounds are always of particular importance. This is why the relatively recent discovery of transition-metal-catalyzed reactions of alkenyl triflates, readily available from enolizable carbonyl precursors, immediately found widespread application.[2] Following this line of research, alkenyl 1,1,2,2,3,3,4,4,4-nonafluorobutane-1-sulfonates (hereinafter referred to alkenyl nonaflates) were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Because the halogen anion is capable of binding easily to [(dppf)Pd(vinyl)(OTf)] to form more stable [(dppf)Pd(vinyl)Br],i ti sl ikely that the addition of KBr facilitates the transmetalation step and the catalytic cycle thereafter.V arious multi-substituted cyclic and acyclicv inyl triflates were difluoromethylated in good to excellent yields under these conditions (Scheme 3). Likewise, reactions of vinyl nonaflates [19] occurred smoothly under these conditions in good yields (Scheme 3, 5c and 5g).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Because the halogen anion is capable of binding easily to [(dppf)Pd(vinyl)(OTf)] to form more stable [(dppf)Pd(vinyl)Br],i ti sl ikely that the addition of KBr facilitates the transmetalation step and the catalytic cycle thereafter.V arious multi-substituted cyclic and acyclicv inyl triflates were difluoromethylated in good to excellent yields under these conditions (Scheme 3). Likewise, reactions of vinyl nonaflates [19] occurred smoothly under these conditions in good yields (Scheme 3, 5c and 5g).…”
mentioning
confidence: 86%
“…Interestingly,t he yield was decreased when the reactiont ime was elongated to 48 ho rt he reaction temperature wasi ncreasedt o6 0 8 Cf or 12 h. We attribute this decrease in the yield of the desired product to the palladium-mediated irreversible oxidative addition of the allylic CÀFb ond in difluoromethylateda lkenes under the basic conditions. In fact, only 40 % yield of the b-difluoromethylated styrene was detected by 19 FNMR spectroscopy when the reaction was carriedo ut in dioxane at 60 8Cf or 4h in the presence of 10 mol %[ Pd(dba) 2 ], 20 mol %D PPF and 1.0 equivalent of NaOtBu. When other activators, such as KF,CsF or TBAF,were used, the yields of the desired product were less than 10 %.…”
mentioning
confidence: 99%
“…Exposure of this mixture to Li naphthalide [15] at À30 8C induced the expected radical-based rearrangement, generating, upon oxidation of the resulting mixture of allylic alcohols using DMP, [16] enone 20 in 79 % overall yield for the two steps. Upon extensive experimentation, it was found that slow addition of allyltrimethylsilane to enone 20 in CH 2 Cl 2 in the presence of TiCl 4 (Hosomi-Sakurai reaction) [17] [18] Reduction of the carbonyl group within the latter compound with DIBAL followed by dehydration (POCl 3 , py) then led to the corresponding acetylenic olefin, which was . subjected to sequential zirconium-promoted carboalumination/iodination [19] (81 % yield) and Pd-catalyzed Negishi coupling [20] with Me 2 Zn (94 % yield) to give intermediate 25 via vinyl iodide 24.…”
Section: Methodsmentioning
confidence: 99%
“…The reduction of OX7 followed by elimination to OX21 proceeded smoothly and as subsequent transformation a Heck reaction with alkenyl nonaflate 10 was performed delivering OX22 . The conversion of OX7 to alkyne OX23 applied the protocol of Lyapkalo et al [ 59 ] using Schwesinger’s base [ 60 ] as crucial reagent. First, the corresponding nonaflate is generated from OX7 that immediately underwent elimination to the alkyne.…”
Section: Reviewmentioning
confidence: 99%